CONTENT AND ESSENCE OF THE CONCEPT OF FUNCTIONAL LITERACY IN PEDAGOGICAL RESEARCH - Sulaymon Obloqulov Makhmayusuf oglu (New modern researchers: modern proposals and solutions, 2025)
The article presents the stages of development of the concept of "literacy". The study has developed the periodicity of the change (evolution) of the concept of "functional literacy" in pedagogical theory and practice in different historical periods. It is shown how, in connection with the increasing demands of society for personal development, the concept of "literacy" has turned into the concept of "functional literacy as the basis for the development of competence". In modern pedagogy, functional literacy is considered as the basis for the development of competence.